Oil From Three Aguaje Morphotypes (Mauritia flexuosa L.f.) Extracted by Supercritical Fluid With CO2: Chemical Composition and Chromatic Properties - Ramos-Escudero, Fernando; Gómez-Coca, Raquel B.; Muñoz, Ana María; Fuente-Carmelino, Luciana De La; Pérez-Camino, María del Carmen (Frontiers in Sustainable Food Systems, 2022)
The chemical composition and CIELAB color parameters of oil from three aguaje morphotypes (Mauritia flexuosa L.f.) extracted by supercritical carbon dioxide was investigated. By chromatography (HPLC and GC), spectrometry (UV/vis), and digital image colorimetry (digital camera), carotenoids, tocopherols, tocotrienols, fatty acids, total polyphenols, and CIELAB color space were analyzed. These findings showed that the oil obtained from morphotype 3 was superior in several analytes (carotenoids, polyphenols, oleic acid, β-sitosterol, campesterol, and stigmasterol), while morphotype 2 and morphotype 1 showed very close profiles. The most similar chemical components in the oils of the three morphotypes were stigmasterol (16.00 to 17.81%), β-sitosterol (66.39 to 68.94%), palmitic acid (15.56 to 20.69%), and oleic acid (73.29 to 79.54%). The chromatic parameters (L*, a*, b*, and Cab*) were quite different except for the hue angle (hab) (66.55 to 69.71 U), which showed some similarity. Aguaje oil is an interesting resource that stands out for its high content of carotenoids. All three morphotypes may be suitable for potential commercial applications.